Digital color management encoding solutions - Giorgianni, Edward J. 1944- (Addison-Wesley, 1998)
The color-imaging industry is on the threshold of major transformation and enormous expansion as digital color technology comes of age, bringing high-quality color to desktop systems and the Internet. However, the technology is not without challenges. In particular, it must contend with an ever-increasing variety of imaging devices and media. At the same time, it must produce predictable color results from individual systems and provide successful exchange of digital color images among different types of systems. Digital Color Management: Encoding Solutions offers engineers, scientists, and programmers practical solutions to these and other challenges of color imaging in the digital domain. Going beyond standard color-measurement techniques, this book describes advanced methods for digitally representing and communicating color. It provides clearly written background on the science of color and imaging technology, a detailed explanation of digital color encoding today, and an examination of the issues involved in creating a truly device-independent, unified, color-managed environment compatible with all major platforms and devices.Combining the expertise of Edward Giorgianni and Thomas Madden, two principal developers of many color-encoding methods and interchange standards used throughout the color-imaging industry, this book provides a first-hand account of the current state of that industry and an insightful look at its future.